Frameshift mutations, neoantigens and tumor-specific CD8+ T cells in microsatellite unstable colorectal cancers. (3rd May 2016) - Maby, Pauline; Galon, Jérôme; Latouche, Jean-Baptiste
ABSTRACT: Microsatellite unstable colorectal cancers (CRC) express frameshift mutation-derived tumor-specific neoantigens. We recently showed that: (i) frameshift mutations were correlated with tumor-infiltrating CD8 + T cell density, (ii) neoantigen-specific cytotoxic T cells could be obtained in patients whose tumors harbored these mutations, underlining the interest of developing personalized immunotherapy strategies in these cancers.